Use of Whole-Genome Sequencing to Unravel the Genetic Diversity of a Prevalent Mycobacterium bovis Spoligotype in a Multi-Host Scenario in Spain - Pozo, Pilar; Lorente-Leal, Victor; Robbe-Austerman, Suelee; Hicks, Jessica; Stuber, Tod; Bezos, Javier; de Juan, Lucia; Saez, Jose Luis; Romero, Beatriz; Alvarez, Julio; , on behalf of the Spanish Network on Surveillance Monitoring of Animal Tuberculosis (Frontiers in Microbiology, 2022)
Despite the efforts invested in the eradication of bovine tuberculosis in Spain, herd prevalence has remained constant in the country during the last 15 years (~1.5-1.9%) due to a combination of epidemiological factors impairing disease control, including between-species transmission. Here, our aim was to investigate the molecular diversity of Mycobacterium bovis isolates belonging to the highly prevalent SB0339 spoligotype in the cattle-wildlife interface in different regions of Spain using whole-genome sequencing (WGS). Genomic data of 136 M. bovis isolates recovered from different animal species (cattle, wild boar, fallow deer, and red deer) and locations between 2005 and 2018 were analyzed to investigate between- and within-species transmission, as well as within-herds. All sequenced isolates differed by 49-88 single nucleotide polymorphisms from their most recent common ancestor. Genetic heterogeneity was geographic rather than host species-specific, as isolates recovered from both cattle and wildlife from a given region were more closely related compared to isolates from the same species but geographically distant. In fact, a strong association between the geographic and the genetic distances separating pairs of M. bovis isolates was found, with a significantly stronger effect when cattle isolates were compared with wildlife or cattle-wildlife isolates in Spain. The same results were obtained in Madrid, the region with the largest number of sequenced isolates, but no differences depending on the host were observed. Within-herd genetic diversity was limited despite the considerable time elapsed between isolations. The detection of closely related strains in different hosts demonstrates the complex between-host transmission dynamics present in endemic areas in Spain. In conclusion, WGS results a valuable tool to track bTB infection at a high resolution and may contribute to achieve its eradication in Spain.